Quinolinyl Thiosemicarbazones and 2-Amino-pyridines as Antitiubercular Agents - Desai, Pratibha; Naik, Bhadresh; Desai, C.M.; Patel, Dinesh (Asian Journal of Chemistry, 2010)
Preparation and antitubercular activity of some quinolinyl thiosemicarbazone and aminopyridine are reported.